Effect of the level of urea and soybean paste on the concentration of proteins during the solid state fermentation of wasted apple (Malus domestica) - Rodr?guez-Muela, C.; D?az, D.; Salvador, F.; Ruiz, O.; Arzola, C.; Flores, A.; La O, Oreste; El?as, Arabel (Cuban Journal of Agricultural Science, 2010)
Two experiments were performed at controlled temperature (28 and 36 ?C) in order to evaluate the level of urea and soybean paste on the solid state fermentation (SSF) of ground wasted apple. Levels of urea (U) of 1.5 and 2 %, and of soybean paste (SP) of 0.0 and 3.5 % were used in the former. The levels were of 1.5 and 2 % for U, and of 3.5 and 7 % for SP in the second experiment. The samples were added 0.2 % ammonium sulfate and 0.5 % mineral and vitamin supplement in both experiments. The variables evaluated were pH, total yeasts, crude protein (CP), and true protein (TP). The results showed increase in pH since 48 h after the start of the fermentation, and there was only effect of addition of soybean paste (P < 0.01) with values of 4.9 and 5.7 for 0 and 3.5 % of soybean paste in the mixture, respectively. The addition of urea did not show effect on this variable. The highest content of yeasts was attained with the combination in the mixture of 2.0 % urea and 3.5 % soybean paste, reaching values of around 4.0 x 108 cel. mL-1 at 168 h after the start of the fermentation. The CP at the end of the fermentation showed differences (P < 0.01) in both experiments by effect of the addition of U and SP. The TP evidenced interaction between the two experiments and showed higher value when the SP was of 3.5 %. This indicated that there is a favorable response in the TP production by addition of 3.5 % of SP to the mixture, only when the level of U is of 1.5 %. It is concluded that, when the fermentation is performed at 28 ?C, the highest content of true protein is obtained with the combination of 1.5 and 3.5 % of urea and soybean paste, respectively. Nevertheless, when the process is undertaken at 36 ?C, the highest content is attained with 2.0 % of urea and 3.5 % of soybean paste. Further research is suggested to determine other values of input and temperature that prove higher productive and economic efficiency. Key words: yeasts, protein, fermentation.